A construction of nonstandard finite difference scheme to fractional differential system - Cardoso, Lislaine Cristina; Santos, Fernando Luiz Pio dos; Camargo, Rubens de Figueiredo (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2022)
In this paper on the nonstandard finite difference technique is proposed to study numerically a fractional differential system. The Grünwald–Letnikov method is used to approximate the fractional derivatives. The model is given by fractional Caputo operator. The numerical results show that numerical solutions are in agree with analytical studies.